SERUM PEPSINOGEN I AND PEPSINOGEN II AS NON-INVASIVE BIOMARKERS FOR THE DIAGNOSIS OF CHRONIC ATROPHIC GASTRITIS - Zornica Gorcheva; Valeriya Racheva; Mirela Vasileva (Peytchinski Publishing, 2022)
Atrophic gastritis, intestinal metaplasia and dysplasia of the gastric mucosa are major risk factors for the development of an intestinal type of gastric cancer. The selection of patients with such lesions could help with early detection and improve better the prognosis. Esophagogastroscopy is the "gold standard" in detecting gastric cancer and precancerous lesions of the stomach. However, this examination is invasive, expensive, and cannot serve as a screening method. Measurement of serum levels of pessinogen I and pessinogen II is used in high-risk populations in Europe and Asia as a non-invasive marker for the diagnosis of chronic atrophic gastritis. A serum pepsinogen I level ≤ 70ng/ml and pepsinogen I/pepsinogen II ratio ≤ 3 are accepted in many countries as values that most accurately identify patients with advanced atrophic gastritis. On the other hand, the differences in the analytical methods used to determine the level of pepsinogens make the interpretation of results and diagnostic validation difficult.